Effect Of Educational Kinesiology Program On Logical Reasoning In Patients With Multiple Sclerosis (International Journal of Environmental Sciences, 2025)
Background: Multiple sclerosis (MS) is usually accompanied by cognitive impairment. Various exercises can result in cognitive improvements. The use of an educational kinesiology program training (EKPT) in cognitive rehabilitation for Multiple sclerosis is unclear. Aim of the study: This study was done to investigate the effects of an educational kinesiology program on cognitive impairment in patients suffering from relapsing-remitting multiple sclerosis (RRMS). Material and methods: A total of 36 patients were chosen at random from the Outpatient Clinics of two places at Cairo University: The Teaching Hospital of Kasr El Aini and the Faculty of Physical Therapy. These patients were diagnosed with mild cognitive impairment due to RRMS. The participants included 20 females and 16 males. Starting in January 2024 and continuing until May 2025. Their ages varied from eighteen to fifty. Complete clinical evaluations were conducted on all individuals utilizing RehaCom screening modules. Results: in comparing among both groups, the study group showed a significant improvement in logical reasoning while control group had no significant improvement in logical reasoning. Conclusion: Educational kinesiology program training is effective in improving logical reasoning in patients with RRMS with mild cognitive impairment.